Analysis of the quality of online resources for parents of children who are late to talk. (April 2020) - Coughler, Caitlin; M Burke, Shauna; Cardy, Janis Oram
Background and aims: Internet usage worldwide has become a primary source of health-related information and an important resource for parents to find advice on how to promote their child's development and well-being. It is important that healthcare professionals understand what information is available to parents online to best support families and children. The current study evaluated the quality of online resources accessible for parents of children who are late to talk. Method: Fifty-four web pages were evaluated for their usability and reliability using the LIDA instrument and Health on the Net Foundation code of conduct certification, and readability using the Flesch Reading Ease Score and Flesch-Kincaid Grade Level. Origin, author(s), target audience, topics discussed, terminology used, and recommendations were also examined. Results: The majority of websites scored within the moderate range (50–90%) for total LIDA scores and usability, but scored in the low range for reliability (<50%). Significantly higher reliability scores ( p  < 0.001) were found for sites with Health on the Net Foundation code of conduct certification. Readability fell within the standard range. The largest proportion of websites were American, written by speech-language pathologists, with the most common topics being milestones, tips and strategies, and red flags. Discrepancies were mostly seen in terminology and misinformation, and when present, usually related to risk factors and causes. Conclusion: Prior to recommending websites to parents, health professionals should consider readability of the content, check that information is up-to-date, and confirm website sources and reputable authorship. Health professionals should also be aware of the types of unclear or inaccurate information to which parents of children who are late to talk may be exposed online.